CN102515744A - A kind of CaCu3Ti4O12 micro-nano fiber and its preparation method - Google Patents

A kind of CaCu3Ti4O12 micro-nano fiber and its preparation method Download PDF

Info

Publication number
CN102515744A
CN102515744A CN2011104117909A CN201110411790A CN102515744A CN 102515744 A CN102515744 A CN 102515744A CN 2011104117909 A CN2011104117909 A CN 2011104117909A CN 201110411790 A CN201110411790 A CN 201110411790A CN 102515744 A CN102515744 A CN 102515744A
Authority
CN
China
Prior art keywords
solution
cacu
micro
electrospinning
fiber
Prior art date
Legal status (The legal status is an assumption and is not a legal conclusion. Google has not performed a legal analysis and makes no representation as to the accuracy of the status listed.)
Granted
Application number
CN2011104117909A
Other languages
Chinese (zh)
Other versions
CN102515744B (en
Inventor
秦大可
顾嫒娟
梁国正
Current Assignee (The listed assignees may be inaccurate. Google has not performed a legal analysis and makes no representation or warranty as to the accuracy of the list.)
Soochow University
Original Assignee
Soochow University
Priority date (The priority date is an assumption and is not a legal conclusion. Google has not performed a legal analysis and makes no representation as to the accuracy of the date listed.)
Filing date
Publication date
Application filed by Soochow University filed Critical Soochow University
Priority to CN 201110411790 priority Critical patent/CN102515744B/en
Publication of CN102515744A publication Critical patent/CN102515744A/en
Application granted granted Critical
Publication of CN102515744B publication Critical patent/CN102515744B/en
Expired - Fee Related legal-status Critical Current
Anticipated expiration legal-status Critical

Links

Images

Landscapes

  • Inorganic Fibers (AREA)
  • Inorganic Compounds Of Heavy Metals (AREA)

Abstract

本发明公开了一种CaCu 3Ti4O12 微纳级纤维及其制备方法,属无机材料技术领域。它包括元素Ca、Cu、Ti和O,它们按摩尔比为1:3:4:12;直径为200~300纳米。其制备方法是:将无水乙醇、四水合硝酸钙及一水合乙酸铜混合后得到溶液A;将聚乙烯吡咯烷酮、无水乙醇、钛酸丁酯及纺丝助剂混合后得到溶液B;将溶液B缓慢滴加到溶液A中,采用静电纺丝工艺制备CaCu 3Ti4O12 微纳级纤维。本发明通过选择和调整各原料及纺丝助剂的配比、控制工艺条件,有效地控制了原料的水解过程,得到的静电纺丝溶液具有可纺性,提供了一种新型的CaCu 3Ti4O12 微纳级纤维。该制备方法工艺简单、条件温和、易于控制、适用面广。

Figure 201110411790

The invention discloses a CaCu 3 Ti 4 O 12 micro-nano fiber and a preparation method thereof, belonging to the technical field of inorganic materials. It includes elements Ca, Cu, Ti and O, and their molar ratio is 1:3:4:12; the diameter is 200-300 nanometers. The preparation method is as follows: mixing absolute ethanol, calcium nitrate tetrahydrate and copper acetate monohydrate to obtain solution A; mixing polyvinylpyrrolidone, absolute ethanol, butyl titanate and spinning aid to obtain solution B; Solution B was slowly added dropwise to solution A, and CaCu 3 Ti 4 O 12 micro-nano fibers were prepared by electrospinning process . The present invention effectively controls the hydrolysis process of raw materials by selecting and adjusting the ratio of raw materials and spinning aids and controlling process conditions, and the obtained electrospinning solution has spinnability, and provides a new type of CaCu 3 Ti 4 O 12 micro-nano fibers. The preparation method has the advantages of simple process, mild conditions, easy control and wide application.

Figure 201110411790

Description

一种CaCu3Ti4O12微纳级纤维及其制备方法A kind of CaCu3Ti4O12 micro-nano fiber and its preparation method

技术领域 technical field

本发明涉及一种无机纤维材料技术,具体涉及一种微纳级陶瓷纤维及其制备方法。The invention relates to an inorganic fiber material technology, in particular to a micro-nano ceramic fiber and a preparation method thereof.

背景技术 Background technique

高介电常数的材料可以用于小体积的电容性器件的制造,为电子器件微型化提供了很大可能,因此其在微型谐振器、滤波器、便携式电话等领域有着很广泛的用途,在微电子工业中起着越来越重要的作用。Materials with high dielectric constant can be used in the manufacture of small-volume capacitive devices, which provides a great possibility for the miniaturization of electronic devices, so it has a wide range of applications in the fields of micro-resonators, filters, mobile phones, etc., in Playing an increasingly important role in the microelectronics industry.

Subramanian等人(M.A. Subramanian,Dong Li,et al. J. Solid State Chemistry,2000,151: 323-325)在2000年发现具有类钙钛矿结构的CaCuSubramanian et al. (M.A. Subramanian, Dong Li, et al. J. Solid State Chemistry, 2000, 151: 323-325) discovered CaCu with a perovskite-like structure in 2000 33 TiTi 44 Oo 1212 (简写为CCTO)在100~500K的温度范围内具有很高的介电常数(一般情况大于10000),并且在很宽的温度范围内,没有结构相变和铁电相变,因此,这种材料在电子行业的应用具有广阔的前景。(abbreviated as CCTO) has a very high dielectric constant (generally greater than 10,000) in the temperature range of 100-500K, and in a wide temperature range, there is no structural phase transition and ferroelectric phase transition. Therefore, this The application of materials in the electronics industry has broad prospects.

以纤维为代表的一维微纳级材料具有特殊的光学性能、电学性能及空间几何结构,是研发具有新型电子传输特性、光学特性和力学性能的理想材料。但是,目前CaCuOne-dimensional micro-nano materials represented by fibers have special optical properties, electrical properties and spatial geometry, and are ideal materials for the development of new electronic transport properties, optical properties and mechanical properties. However, currently CaCu 33 TiTi 44 Oo 1212 局限于陶瓷烧结体、粉末和薄膜等存在形式,还未见关于CaCuIt is limited to the existing forms of ceramic sintered body, powder and film, and there is no information about CaCu 33 TiTi 44 Oo 1212 微纳级纤维的报道,使之在传感器等高新领域的应用受限。The reports of micro-nano fibers limit their application in high-tech fields such as sensors.

目前,制备CaCuCurrently, the preparation of CaCu 33 TiTi 44 Oo 1212 样品的方法主要是固体烧结法、溶胶凝胶法和脉冲激光沉积法。固体烧结法通过机械研磨法制备各组分的超细粉体,然后通过高温固相烧结制备成致密的微晶陶瓷;但是该方法制备工艺严苛,只有精确控制,才能获得介电常数稳定的CaCuThe sample methods are mainly solid sintering method, sol-gel method and pulsed laser deposition method. The solid sintering method prepares ultra-fine powders of each component by mechanical grinding, and then prepares dense microcrystalline ceramics by high-temperature solid-phase sintering; CaCu 33 TiTi 44 Oo 1212 陶瓷。溶胶凝胶法是制备均匀纳米超细粉体的有效方法,具有纯度高,各组分分子级化学均匀、颗粒大小可控、设备简单等特点。脉冲激光沉积可以原位生长高温超导薄膜,无论是在制备薄膜材料还是纳米结构的材料方面都具有广阔的应用前景。但在制备更高质量的纳米材料方面还有不小的困难,并且由于研究时间较短,如何更加容易、简单地控制形成纳米结构以及纳米结构的生长机理,都需要进行进一步探索。上述三种方法都无法得到CaCuceramics. The sol-gel method is an effective method for preparing uniform nano-ultrafine powder, which has the characteristics of high purity, molecular chemical uniformity of each component, controllable particle size, and simple equipment. Pulsed laser deposition can grow high-temperature superconducting thin films in situ, and has broad application prospects in the preparation of thin film materials and nanostructured materials. However, there are still many difficulties in preparing higher-quality nanomaterials, and due to the short research time, how to control the formation of nanostructures and the growth mechanism of nanostructures more easily and simply needs to be further explored. None of the above three methods can obtain CaCu 33 TiTi 44 Oo 1212 微纳级纤维。micro-nano fibers.

近年来,静电纺丝技术受到人们的广泛关注,它是一种通过高压静电来获得纤维的方法,其核心是使带电荷的纺丝液在静电场中流动与变形,随着溶剂蒸发或熔体冷却而固化,从而得到纤维。与其他方法相比,静电纺丝具有明显的优势。例如,制备的纤维长径比很大,纤维长度可以达到宏观尺度;制备条件温和、速度较快、产量较大,适用面广泛,而且制备过程非常简单,是制备纤维非常有效、简便的方法。在本发明做出之前,中国发明专利(CN102084044A)公开了一种通过溶液的静电纺丝生产无机纳米纤维的方法,该溶液包括溶于以醇为基础的溶剂体系中的金属或半金属或非金属的烷氧基化物。溶液被防止烷氧基化物的水解的螯合剂所稳定化,在均化之后该溶液与由聚(乙烯基吡咯烷酮)在醇中的溶液进行混合,然后所得溶液被输送至静电场,在其中连续进行静电纺丝,纺丝的结果是有机-无机纳米纤维的生产,该纤维然后在纺丝设备之外在500~1300℃的温度下在空气氛围中进行煅烧。中国发明专利“ 一种静电纺丝制备氧化铝纳米纤维的方法”(CN 101982581A)将聚合物溶于溶剂中,再将乙酰丙酮铝加入到聚合物溶液中,制备纺丝溶液,经静电纺丝和烧结处理,得到氧化铝纳米纤维。上述技术方案提供的是制备简单氧化物的纤维,而CaCuIn recent years, electrospinning technology has received widespread attention. It is a method of obtaining fibers through high-voltage static electricity. Its core is to make the charged spinning solution flow and deform in an electrostatic field. The body is cooled and solidified to obtain fibers. Electrospinning has distinct advantages over other methods. For example, the aspect ratio of the prepared fiber is very large, and the fiber length can reach the macro scale; the preparation conditions are mild, the speed is fast, the output is large, the application is wide, and the preparation process is very simple, which is a very effective and convenient method for preparing fibers. Prior to the present invention, a Chinese invention patent (CN102084044A) disclosed a method for producing inorganic nanofibers by electrospinning of a solution comprising metal or semimetal or non- metal alkoxides. The solution is stabilized by a chelating agent that prevents the hydrolysis of the alkoxylates, after homogenization the solution is mixed with a solution of poly(vinylpyrrolidone) in alcohol, and the resulting solution is delivered to an electrostatic field where continuous Electrospinning is performed, the result of which is the production of organic-inorganic nanofibers, which are then calcined outside the spinning equipment at a temperature of 500-1300°C in an air atmosphere. Chinese invention patent "A method for preparing alumina nanofibers by electrospinning" (CN 101982581A) dissolves the polymer in a solvent, and then adds aluminum acetylacetonate to the polymer solution to prepare a spinning solution, which is electrospun and sintering treatment to obtain alumina nanofibers. What above-mentioned technical scheme provides is to prepare the fiber of simple oxide, and CaCu 33 TiTi 44 Oo 1212 陶瓷由三种金属元素按固定比例组成,用以钛的烷氧基化合物及钙和铜对应的无机盐作为原料时,由于钙和铜的无机盐中含有结晶水及其本身所具有的吸水性,将导致金属烷氧基化合物快速地水解和聚合,甚至产生部分凝胶,使纺丝液的粘度呈几何级数上升,远远超出可以进行静电纺丝的范围,这种现象极容易发生在纺丝前,给静电纺丝工艺带来了困难,甚至使静电纺丝无法进行,因此,目前未见有CaCuCeramics are composed of three metal elements in a fixed ratio. When titanium alkoxides and inorganic salts corresponding to calcium and copper are used as raw materials, the inorganic salts of calcium and copper contain crystal water and their own water absorption. , will lead to rapid hydrolysis and polymerization of metal alkoxylates, and even produce some gels, so that the viscosity of the spinning solution increases geometrically, far beyond the range that can be used for electrospinning. This phenomenon is very easy to occur in Before spinning, it brings difficulties to the electrospinning process, and even makes electrospinning impossible. Therefore, there is no CaCu 33 TiTi 44 Oo 1212 纳米纤维的使用,在现有技术中,也未见关于静电纺丝方法制备CaCuThe use of nanofibers, in the prior art, has not been seen about the electrospinning method to prepare CaCu 33 TiTi 44 Oo 1212 微纳级纤维的报道。Report on micro-nano fibers.

发明内容 Contents of the invention

为了克服现有技术存在的不足,本发明的目的在于提供一种CaCuIn order to overcome the deficiencies in the prior art, the object of the present invention is to provide a CaCu 33 TiTi 44 Oo 1212 微纳级纤维,以及一种工艺简单、条件温和、适用面广的CaCuMicro-nano fibers, and a CaCu with simple process, mild conditions and wide application 33 TiTi 44 Oo 1212 微纳级纤维的制备方法。Preparation method of micro-nano fibers.

实现本发明目的所采用的技术方案是提供一种CaCuThe technical solution adopted to realize the object of the invention is to provide a CaCu 33 TiTi 44 Oo 1212 微纳级纤维,它包括元素Ca、Cu、Ti和O,它们的按摩尔比为1:3:4:12;,纤维直径为200~300纳米。Micro-nano fiber, which includes elements Ca, Cu, Ti and O, and their molar ratio is 1:3:4:12; the diameter of the fiber is 200-300 nanometers.

一种CaCua CaCu 33 TiTi 44 Oo 1212 微纳级纤维的制备方法,包括如下步骤: A preparation method for micro-nano fibers, comprising the steps of:

1、在搅拌条件下,按重量计,将100~200份无水乙醇、1~5份四水合硝酸钙及2~10份一水合乙酸铜加入到反应容器中,在20~50℃的温度条件下恒温反应1~5小时,得到溶液A;1. Under stirring conditions, by weight, add 100-200 parts of absolute ethanol, 1-5 parts of calcium nitrate tetrahydrate and 2-10 parts of copper acetate monohydrate into the reaction vessel. Under the condition of constant temperature reaction for 1 to 5 hours, the solution A is obtained;

2、在搅拌条件下,按重量计,将5~30份聚乙烯吡咯烷酮、100~200份无水乙醇、3~15份纺丝助剂及3~15份钛酸丁酯加入到反应容器中,在20~50℃的温度条件下恒温反应1~3小时,得到溶液B;2. Under stirring conditions, add 5-30 parts of polyvinylpyrrolidone, 100-200 parts of absolute ethanol, 3-15 parts of spinning aid and 3-15 parts of butyl titanate into the reaction vessel by weight , reacting at a constant temperature for 1 to 3 hours at a temperature of 20 to 50° C. to obtain a solution B;

3、在搅拌条件下,将溶液B缓慢滴加到溶液A中,得到静电纺丝溶液;3. Slowly add solution B to solution A under stirring conditions to obtain an electrospinning solution;

4、采用静电纺丝工艺得到纤维;4. The fiber is obtained by electrospinning process;

5、将静电纺丝得到的纤维在50~70℃下干燥12~18小时,再以5~10℃/分钟的升温速率加热到900~1000℃,并恒温2~5小时,得到CaCu5. Dry the fiber obtained by electrospinning at 50-70°C for 12-18 hours, then heat it to 900-1000°C at a heating rate of 5-10°C/min, and keep the temperature constant for 2-5 hours to obtain CaCu 33 TiTi 44 Oo 1212 微纳级纤维。micro-nano fibers.

所述的纺丝助剂为乙酸、四甲基氢氧化铵,或氢氧化钾中的一种。The spinning aid is one of acetic acid, tetramethylammonium hydroxide, or potassium hydroxide.

静电纺丝工艺为电压15~30千伏,固化距离5~15厘米,接收装置为铝箔。The electrospinning process uses a voltage of 15-30 kV, a curing distance of 5-15 cm, and the receiving device is aluminum foil.

与现有技术相比,本发明具有的有益效果是:提供了一种CaCuCompared with the prior art, the present invention has the beneficial effect of providing a CaCu 33 TiTi 44 Oo 1212 纤维,它是CaCufiber, which is CaCu 33 TiTi 44 Oo 1212 的一种新的存在形式。本发明通过调整各实验原料的配比、添加方式和纺丝助剂,有效地控制原料的水解过程,使静电纺丝过程顺利进行。所提出的制备方法具有工艺简单、条件温和、易于控制、适用面广的特点。a new form of existence. The invention effectively controls the hydrolysis process of the raw materials by adjusting the ratio of the experimental raw materials, the addition method and the spinning auxiliary agent, so that the electrospinning process can be carried out smoothly. The proposed preparation method has the characteristics of simple process, mild conditions, easy control and wide application.

附图说明 Description of drawings

图1是本发明实施例1提供的CaCuFig. 1 is the CaCu that the embodiment of the present invention 1 provides 33 TiTi 44 Oo 1212 微纳级纤维的SEM图;SEM images of micro-nano fibers;

图2是本发明实施例1提供的CaCuFig. 2 is the CaCu that the embodiment of the present invention 1 provides 33 TiTi 44 Oo 1212 微纳级纤维的XRD图;XRD patterns of micro-nano fibers;

图3是本发明实施例5提供的CaCuFig. 3 is the CaCu that the embodiment of the present invention 5 provides 33 TiTi 44 Oo 1212 微纳级纤维的SEM图;SEM images of micro-nano fibers;

图4是本发明实施例5提供的CaCuFig. 4 is the CaCu that the embodiment of the present invention 5 provides 33 TiTi 44 Oo 1212 微纳级纤维的XRD图;XRD patterns of micro-nano fibers;

图5是本发明实施例8提供的CaCuFig. 5 is the CaCu that the embodiment of the present invention 8 provides 33 TiTi 44 Oo 1212 微纳级纤维的SEM图;SEM images of micro-nano fibers;

图6是本发明实施例8提供的CaCuFig. 6 is the CaCu that the embodiment of the present invention 8 provides 33 TiTi 44 Oo 1212 微纳级纤维的XRD图。XRD patterns of micro-nano fibers.

具体实施方式 Detailed ways

下面结合附图和实施例对本发明技术方案作进一步描述。The technical solutions of the present invention will be further described below in conjunction with the accompanying drawings and embodiments.

实施例1Example 1

1、在搅拌条件下,将10毫升无水乙醇、1.04克四水合硝酸钙及2.63克一水合乙酸铜加入到反应容器中,在30℃的温度条件下恒温反应2小时,得到溶液A;1. Under stirring conditions, add 10 ml of absolute ethanol, 1.04 g of calcium nitrate tetrahydrate and 2.63 g of copper acetate monohydrate into the reaction vessel, and react at a constant temperature of 30°C for 2 hours to obtain solution A;

2、在搅拌条件下,将1.5克聚乙烯吡咯烷酮、10毫升无水乙醇、3毫升乙酸及6毫升钛酸丁酯加入到反应容器中,在30℃的温度条件下恒温反应1小时,得到溶液B;2. Under stirring conditions, add 1.5 g of polyvinylpyrrolidone, 10 ml of absolute ethanol, 3 ml of acetic acid and 6 ml of butyl titanate into the reaction vessel, and react at a constant temperature of 30 ° C for 1 hour to obtain a solution B;

3、在搅拌条件下,将步骤2中制得的溶液B全部缓慢滴加到溶液A中,滴加速度为每小时滴加100毫升,得到溶液C;3. Under stirring conditions, all the solution B prepared in step 2 was slowly added dropwise to solution A at a rate of 100 ml per hour to obtain solution C;

4、将溶液C进行静电纺丝,静电纺丝使用的电压为16.50千伏,进样速率为6.5毫升/小时,固化距离为12厘米,接收装置为铝箔,静电纺丝时间为3小时,得到相应的纤维;4. Electrospinning solution C, the voltage used for electrospinning is 16.50 kV, the injection rate is 6.5 ml/hour, the curing distance is 12 cm, the receiving device is aluminum foil, and the electrospinning time is 3 hours. corresponding fibers;

5、将静电纺丝得到的纤维在60℃下干燥15小时,然后以5℃/分钟的升温速率加热到900℃,并恒温3小时,得到新型CaCu5. Dry the fiber obtained by electrospinning at 60°C for 15 hours, then heat it to 900°C at a heating rate of 5°C/min, and keep the temperature constant for 3 hours to obtain a new type of CaCu 33 TiTi 44 Oo 1212 纤维。fiber.

参见附图1是实施例1提供的CaCuReferring to accompanying drawing 1 is the CaCu that embodiment 1 provides 33 TiTi 44 Oo 1212 纤维的SEM图,可以看出,CaCuSEM image of the fiber, it can be seen that CaCu 33 TiTi 44 Oo 1212 为纤维形式存在,直径约为200~300纳米。It exists in the form of fibers with a diameter of about 200-300 nanometers.

参见附图2是本实施例CaCuReferring to accompanying drawing 2 is present embodiment CaCu 33 TiTi 44 Oo 1212 纤维的XRD图,从中可以看出,CaCuThe XRD pattern of the fiber, from which it can be seen that the CaCu 33 TiTi 44 Oo 1212 纤维的结构是纯CaCuThe structure of the fiber is pure CaCu 33 TiTi 44 Oo 1212 相。Mutually.

实施例2Example 2

1、在搅拌条件下,将15毫升无水乙醇、1.04克四水合硝酸钙及2.63克一水合乙酸铜加入到反应容器中,在45℃的温度条件下恒温反应3小时,得到溶液A;1. Under stirring conditions, add 15 ml of absolute ethanol, 1.04 g of calcium nitrate tetrahydrate and 2.63 g of copper acetate monohydrate into the reaction vessel, and react at a constant temperature of 45°C for 3 hours to obtain solution A;

2、在搅拌条件下,将2.5克聚乙烯吡咯烷酮、15毫升无水乙醇1.5克四甲基氢氧化铵及6毫升钛酸丁酯加入到反应容器中,在45℃的温度条件下恒温反应3小时,得到溶液B;2. Under stirring conditions, add 2.5 grams of polyvinylpyrrolidone, 15 milliliters of absolute ethanol, 1.5 grams of tetramethylammonium hydroxide and 6 milliliters of butyl titanate into the reaction vessel, and react at a constant temperature of 45°C for 3 Hour, obtain solution B;

3、在搅拌条件下,将步骤2中制得的溶液B全部缓慢滴加到溶液A中,滴加速度为每小时滴加200毫升,得到溶液C;3. Under stirring conditions, slowly add all the solution B prepared in step 2 to solution A at a rate of 200 ml per hour to obtain solution C;

4、将溶液C进行静电纺丝,静电纺丝使用的电压为19.50千伏,进样速率为8.5毫升/小时,固化距离为15厘米,接收装置为铝箔,静电纺丝时间为2小时,得到相应的纤维;4. Electrospinning solution C, the voltage used for electrospinning is 19.50 kV, the injection rate is 8.5 ml/hour, the curing distance is 15 cm, the receiving device is aluminum foil, and the electrospinning time is 2 hours. corresponding fibers;

5、将静电纺丝得到的纤维在70℃下干燥18小时,然后以10℃/分钟的升温速率加热到950℃,并恒温5小时,得到新型CaCu5. Dry the fiber obtained by electrospinning at 70°C for 18 hours, then heat it to 950°C at a heating rate of 10°C/min, and keep the temperature constant for 5 hours to obtain a new type of CaCu 33 TiTi 44 Oo 1212 纤维。fiber.

实施例3Example 3

1、在搅拌条件下,将20毫升无水乙醇、2.08克四水合硝酸钙及5.26克一水合乙酸铜加入到反应容器中,在50℃的温度条件下恒温反应1小时,得到溶液A;1. Under stirring conditions, add 20 ml of absolute ethanol, 2.08 g of calcium nitrate tetrahydrate and 5.26 g of copper acetate monohydrate into the reaction vessel, and react at a constant temperature of 50° C. for 1 hour to obtain solution A;

2、在搅拌条件下,将3克聚乙烯吡咯烷酮、20毫升无水乙醇3克四甲基氢氧化铵及12毫升钛酸丁酯加入到反应容器中,在50℃的温度条件下恒温反应1小时,得到溶液B;2. Under stirring conditions, add 3 grams of polyvinylpyrrolidone, 20 milliliters of absolute ethanol, 3 grams of tetramethylammonium hydroxide and 12 milliliters of butyl titanate into the reaction vessel, and react at a constant temperature of 50 ° C for 1 Hour, obtain solution B;

3、在搅拌条件下,将步骤2中制得的溶液B全部缓慢滴加到溶液A中,滴加速度为每小时滴加150毫升,得到溶液C;3. Under stirring conditions, all the solution B prepared in step 2 was slowly added dropwise to solution A at a rate of 150 ml per hour to obtain solution C;

4、将溶液C进行静电纺丝,静电纺丝使用的电压为23.50千伏,进样速率为9.5毫升/小时,固化距离为15厘米,接收装置为铝箔,静电纺丝时间为2小时,得到相应的纤维;4. Electrospinning solution C, the voltage used for electrospinning is 23.50 kV, the injection rate is 9.5 ml/hour, the curing distance is 15 cm, the receiving device is aluminum foil, and the electrospinning time is 2 hours. corresponding fibers;

5、将静电纺丝得到的纤维在50℃下干燥12小时,然后以7℃/分钟的升温速率加热到1000℃,并恒温2小时,得到新型CaCu5. Dry the fiber obtained by electrospinning at 50°C for 12 hours, then heat it to 1000°C at a heating rate of 7°C/min, and keep the temperature constant for 2 hours to obtain a new type of CaCu 33 TiTi 44 Oo 1212 纤维。fiber.

实施例4Example 4

1、在搅拌条件下,将15毫升无水乙醇、1.56克四水合硝酸钙及3.95克一水合乙酸铜加入到反应容器中,在20℃的温度条件下恒温反应1小时,得到溶液A;1. Under stirring conditions, add 15 ml of absolute ethanol, 1.56 g of calcium nitrate tetrahydrate and 3.95 g of copper acetate monohydrate into the reaction vessel, and react at a constant temperature of 20°C for 1 hour to obtain solution A;

2、在搅拌条件下,将1.9克聚乙烯吡咯烷酮、18毫升无水乙醇1克氢氧化钾及9毫升钛酸丁酯加入到反应容器中,在20℃的温度条件下恒温反应1小时,得到溶液B;2. Under stirring conditions, add 1.9 grams of polyvinylpyrrolidone, 18 milliliters of absolute ethanol, 1 gram of potassium hydroxide and 9 milliliters of butyl titanate into the reaction vessel, and react at a constant temperature of 20 ° C for 1 hour to obtain Solution B;

3、在搅拌条件下,将步骤2中制得的溶液B全部缓慢滴加到溶液A中,滴加速度为每小时滴加200毫升,得到溶液C;3. Under stirring conditions, slowly add all the solution B prepared in step 2 to solution A at a rate of 200 ml per hour to obtain solution C;

4、将溶液C进行静电纺丝,静电纺丝使用的电压为27.50千伏,进样速率为8.5毫升/小时,固化距离为12厘米,接收装置为铝箔,静电纺丝时间为2小时,得到相应的纤维;4. Electrospinning solution C, the voltage used for electrospinning is 27.50 kV, the injection rate is 8.5 ml/hour, the curing distance is 12 cm, the receiving device is aluminum foil, and the electrospinning time is 2 hours. corresponding fibers;

5、将静电纺丝得到的纤维在70℃下干燥18小时,然后以9℃/分钟的升温速率加热到1000℃,并恒温3小时,得到新型CaCu5. Dry the fiber obtained by electrospinning at 70°C for 18 hours, then heat it to 1000°C at a heating rate of 9°C/min, and keep the temperature constant for 3 hours to obtain a new type of CaCu 33 TiTi 44 Oo 1212 纤维。fiber.

实施例5Example 5

1、在搅拌条件下,将20毫升无水乙醇、1.56克四水合硝酸钙及3.95克一水合乙酸铜加入到反应容器中,在50℃的温度条件下恒温反应1小时,得到溶液A;1. Under stirring conditions, add 20 ml of absolute ethanol, 1.56 g of calcium nitrate tetrahydrate and 3.95 g of copper acetate monohydrate into the reaction vessel, and react at a constant temperature of 50°C for 1 hour to obtain solution A;

2、在搅拌条件下,将3克聚乙烯吡咯烷酮、20毫升无水乙醇1.5克氢氧化钾及9毫升钛酸丁酯加入到反应容器中,在20℃的温度条件下恒温反应3小时,得到溶液B;2. Add 3 grams of polyvinylpyrrolidone, 20 milliliters of absolute ethanol, 1.5 grams of potassium hydroxide and 9 milliliters of butyl titanate into the reaction vessel under stirring conditions, and react at a constant temperature of 20°C for 3 hours to obtain Solution B;

3、在搅拌条件下,将步骤2中制得的溶液B全部缓慢滴加到溶液A中,滴加速度为每小时滴加200毫升,得到溶液C;3. Under stirring conditions, slowly add all the solution B prepared in step 2 to solution A at a rate of 200 ml per hour to obtain solution C;

4、将溶液C进行静电纺丝,静电纺丝使用的电压为30千伏,进样速率为10毫升/小时,固化距离为15厘米,接收装置为铝箔,静电纺丝时间为2小时,得到相应的纤维;4. Electrospinning the solution C, the voltage used for electrospinning is 30 kV, the injection rate is 10 ml/hour, the curing distance is 15 cm, the receiving device is aluminum foil, and the electrospinning time is 2 hours, the obtained corresponding fibers;

5、将静电纺丝得到的纤维在70℃下干燥18小时,然后以5℃/分钟的升温速率加热到1000℃,并恒温3小时,得到新型CaCu5. Dry the fiber obtained by electrospinning at 70°C for 18 hours, then heat it to 1000°C at a heating rate of 5°C/min, and keep the temperature constant for 3 hours to obtain a new type of CaCu 33 TiTi 44 Oo 1212 纤维。fiber.

参见附图3和4分别是本实施例提供的CaCuReferring to accompanying drawing 3 and 4 is the CaCu that present embodiment provides respectively 33 TiTi 44 Oo 1212 纤维的SEM图和XRD图,可以看出,CaCuThe SEM image and XRD image of the fiber, it can be seen that CaCu 33 TiTi 44 Oo 1212 为纤维形式存在并且是纯CaCuExists in fiber form and is pure CaCu 33 TiTi 44 Oo 1212 相,直径约为200~300纳米。phase with a diameter of about 200 to 300 nanometers.

实施例6Example 6

1、在搅拌条件下,将20毫升无水乙醇、1.56克四水合硝酸钙及3.95克一水合乙酸铜加入到反应容器中,在20℃的温度条件下恒温反应5小时,得到溶液A;1. Under stirring conditions, add 20 ml of absolute ethanol, 1.56 g of calcium nitrate tetrahydrate and 3.95 g of copper acetate monohydrate into the reaction vessel, and react at a constant temperature of 20°C for 5 hours to obtain solution A;

2、在搅拌条件下,将1.3克聚乙烯吡咯烷酮、20毫升无水乙醇0.5克氢氧化钾及9毫升钛酸丁酯加入到反应容器中,在20℃的温度条件下恒温反应3小时,得到溶液B;2. Under stirring conditions, add 1.3 grams of polyvinylpyrrolidone, 20 milliliters of absolute ethanol, 0.5 grams of potassium hydroxide and 9 milliliters of butyl titanate into the reaction vessel, and react at a constant temperature of 20 ° C for 3 hours to obtain Solution B;

3、在搅拌条件下,将步骤2中制得的溶液B全部缓慢滴加到溶液A中,滴加速度为每小时滴加200毫升,得到溶液C;3. Under stirring conditions, slowly add all the solution B prepared in step 2 to solution A at a rate of 200 ml per hour to obtain solution C;

4、将溶液C进行静电纺丝,静电纺丝使用的电压为15千伏,进样速率为1毫升/小时,固化距离为5厘米,接收装置为铝箔,静电纺丝时间为5小时,得到相应的纤维;4. Electrospinning solution C, the voltage used for electrospinning is 15 kV, the injection rate is 1 ml/hour, the curing distance is 5 cm, the receiving device is aluminum foil, and the electrospinning time is 5 hours, and the obtained corresponding fibers;

5、将静电纺丝得到的纤维在50℃下干燥12小时,然后以10℃/分钟的升温速率加热到900℃,并恒温5小时,得到新型CaCu5. Dry the fiber obtained by electrospinning at 50°C for 12 hours, then heat it to 900°C at a heating rate of 10°C/min, and keep the temperature constant for 5 hours to obtain a new type of CaCu 33 TiTi 44 Oo 1212 纤维。fiber.

实施例7Example 7

1、在搅拌条件下,将10毫升无水乙醇、0.78克四水合硝酸钙及1.98克一水合乙酸铜加入到反应容器中,在20℃的温度条件下恒温反应5小时,得到溶液A;1. Under stirring conditions, add 10 ml of absolute ethanol, 0.78 g of calcium nitrate tetrahydrate and 1.98 g of copper acetate monohydrate into the reaction vessel, and react at a constant temperature of 20°C for 5 hours to obtain solution A;

2、在搅拌条件下,将0.5克聚乙烯吡咯烷酮、10毫升无水乙醇0.8毫升乙酸及4.5毫升钛酸丁酯加入到反应容器中,在20℃的温度条件下恒温反应3小时,得到溶液B;2. Under stirring conditions, add 0.5 g of polyvinylpyrrolidone, 10 ml of absolute ethanol, 0.8 ml of acetic acid and 4.5 ml of butyl titanate into the reaction vessel, and react at a constant temperature of 20 ° C for 3 hours to obtain solution B ;

3、在搅拌条件下,将步骤2中制得的溶液B全部缓慢滴加到溶液A中,滴加速度为每小时滴加100毫升,得到溶液C;3. Under stirring conditions, all the solution B prepared in step 2 was slowly added dropwise to solution A at a rate of 100 ml per hour to obtain solution C;

4、将溶液C进行静电纺丝,静电纺丝使用的电压为15千伏,进样速率为2.3毫升/小时,固化距离为10厘米,接收装置为铝箔,静电纺丝时间为5小时,得到相应的纤维;4. Electrospinning solution C, the voltage used for electrospinning is 15 kV, the injection rate is 2.3 ml/hour, the curing distance is 10 cm, the receiving device is aluminum foil, and the electrospinning time is 5 hours. corresponding fibers;

5、将静电纺丝得到的纤维在60℃下干燥12小时,然后以5℃/分钟的升温速率加热到950℃,并恒温2小时,得到新型CaCu5. Dry the fiber obtained by electrospinning at 60°C for 12 hours, then heat it to 950°C at a heating rate of 5°C/min, and keep the temperature constant for 2 hours to obtain a new type of CaCu 33 TiTi 44 Oo 1212 纤维。fiber.

实施例8Example 8

1、在搅拌条件下,将20毫升无水乙醇、2.08克四水合硝酸钙及5.26克一水合乙酸铜加入到反应容器中,在30℃的温度条件下恒温反应1小时,得到溶液A;1. Under stirring conditions, add 20 ml of absolute ethanol, 2.08 g of calcium nitrate tetrahydrate and 5.26 g of copper acetate monohydrate into the reaction vessel, and react at a constant temperature of 30°C for 1 hour to obtain solution A;

2、在搅拌条件下,将2.5克聚乙烯吡咯烷酮、15毫升无水乙醇1.5克四甲基氢氧化铵及12毫升钛酸丁酯加入到反应容器中,在50℃的温度条件下恒温反应1小时,得到溶液B;2. Under stirring conditions, add 2.5 grams of polyvinylpyrrolidone, 15 milliliters of absolute ethanol, 1.5 grams of tetramethylammonium hydroxide and 12 milliliters of butyl titanate into the reaction vessel, and react at a constant temperature of 50 ° C for 1 Hour, obtain solution B;

3、在搅拌条件下,将步骤2中制得的溶液B全部缓慢滴加到溶液A中,滴加速度为每小时滴加150毫升,得到溶液C;3. Under stirring conditions, all the solution B prepared in step 2 was slowly added dropwise to solution A at a rate of 150 ml per hour to obtain solution C;

4、将溶液C进行静电纺丝,静电纺丝使用的电压为23.50千伏,进样速率为9.5毫升/小时,固化距离为15厘米,接收装置为铝箔,静电纺丝时间为2小时,得到相应的纤维;4. Electrospinning solution C, the voltage used for electrospinning is 23.50 kV, the injection rate is 9.5 ml/hour, the curing distance is 15 cm, the receiving device is aluminum foil, and the electrospinning time is 2 hours. corresponding fibers;

5、将静电纺丝得到的纤维在50℃下干燥12小时,然后以5℃/分钟的升温速率加热到950℃,并恒温2小时,得到新型CaCu5. Dry the fiber obtained by electrospinning at 50°C for 12 hours, then heat it to 950°C at a heating rate of 5°C/min, and keep the temperature constant for 2 hours to obtain a new type of CaCu 33 TiTi 44 Oo 1212 纤维。fiber.

参见附图5和6,分别是本实施例提供的CaCuReferring to accompanying drawing 5 and 6, it is the CaCu that present embodiment provides respectively 33 TiTi 44 Oo 1212 纤维的SEM图和XRD图,可以看出,CaCuThe SEM image and XRD image of the fiber, it can be seen that CaCu 33 TiTi 44 Oo 1212 为纤维形式存在并且是纯CaCuExists in fiber form and is pure CaCu 33 TiTi 44 Oo 1212 相,直径约为200~300纳米。phase with a diameter of about 200 to 300 nanometers.

实施例9Example 9

1、在搅拌条件下,将18毫升无水乙醇、1.04克四水合硝酸钙及2.63克一水合乙酸铜加入到反应容器中,在35℃的温度条件下恒温反应3小时,得到溶液A;1. Under stirring conditions, add 18 ml of absolute ethanol, 1.04 g of calcium nitrate tetrahydrate and 2.63 g of copper acetate monohydrate into the reaction vessel, and react at a constant temperature of 35°C for 3 hours to obtain solution A;

2、在搅拌条件下,将2.1克聚乙烯吡咯烷酮、18毫升无水乙醇1.8克四甲基氢氧化铵及6毫升钛酸丁酯加入到反应容器中,在45℃的温度条件下恒温反应3小时,得到溶液B;2. Under stirring conditions, add 2.1 grams of polyvinylpyrrolidone, 18 milliliters of absolute ethanol, 1.8 grams of tetramethylammonium hydroxide and 6 milliliters of butyl titanate into the reaction vessel, and react at a constant temperature of 45°C for 3 Hour, obtain solution B;

3、在搅拌条件下,将步骤2中制得的溶液B全部缓慢滴加到溶液A中,滴加速度为每小时滴加100毫升,得到溶液C;3. Under stirring conditions, all the solution B prepared in step 2 was slowly added dropwise to solution A at a rate of 100 ml per hour to obtain solution C;

4、将溶液C进行静电纺丝,静电纺丝使用的电压为22.50千伏,进样速率为7.5毫升/小时,固化距离为17厘米,接收装置为铝箔,静电纺丝时间为2小时,得到相应的纤维;4. Electrospinning solution C, the voltage used for electrospinning is 22.50 kV, the injection rate is 7.5 ml/hour, the curing distance is 17 cm, the receiving device is aluminum foil, and the electrospinning time is 2 hours. corresponding fibers;

5、将静电纺丝得到的纤维在70℃下干燥18小时,然后以10℃/分钟的升温速率加热到900℃,并恒温4小时,得到新型CaCu5. Dry the fiber obtained by electrospinning at 70°C for 18 hours, then heat it to 900°C at a heating rate of 10°C/min, and keep the temperature constant for 4 hours to obtain a new type of CaCu 33 TiTi 44 Oo 1212 纤维。fiber.

实施例10Example 10

1、在搅拌条件下,将13毫升无水乙醇、1.04克四水合硝酸钙及2.63克一水合乙酸铜加入到反应容器中,在45℃的温度条件下恒温反应3小时,得到溶液A;1. Under stirring conditions, add 13 ml of absolute ethanol, 1.04 g of calcium nitrate tetrahydrate and 2.63 g of copper acetate monohydrate into the reaction vessel, and react at a constant temperature of 45°C for 3 hours to obtain solution A;

2、在搅拌条件下,将1.9克聚乙烯吡咯烷酮、13毫升无水乙醇1.1克四甲基氢氧化铵及6毫升钛酸丁酯加入到反应容器中,在45℃的温度条件下恒温反应3小时,得到溶液B;2. Under stirring conditions, add 1.9 grams of polyvinylpyrrolidone, 13 milliliters of absolute ethanol, 1.1 grams of tetramethylammonium hydroxide and 6 milliliters of butyl titanate into the reaction vessel, and react at a constant temperature of 45°C for 3 Hour, obtain solution B;

3、在搅拌条件下,将步骤2中制得的溶液B全部缓慢滴加到溶液A中,滴加速度为每小时滴加200毫升,得到溶液C;3. Under stirring conditions, all the solution B prepared in step 2 was slowly added dropwise to solution A at a rate of 200 ml per hour to obtain solution C;

4、将溶液C进行静电纺丝,静电纺丝使用的电压为21.50千伏,进样速率为9.5毫升/小时,固化距离为16厘米,接收装置为铝箔,静电纺丝时间为2小时,得到相应的纤维;4. Electrospinning solution C, the voltage used for electrospinning is 21.50 kV, the injection rate is 9.5 ml/hour, the curing distance is 16 cm, the receiving device is aluminum foil, and the electrospinning time is 2 hours. corresponding fibers;

5、将静电纺丝得到的纤维在65℃下干燥15小时,然后以5℃/分钟的升温速率加热到950℃,并恒温4小时,得到新型CaCu5. Dry the fiber obtained by electrospinning at 65°C for 15 hours, then heat it to 950°C at a heating rate of 5°C/min, and keep the temperature constant for 4 hours to obtain a new type of CaCu 33 TiTi 44 Oo 1212 纤维。fiber.

Claims (4)

1. CaCu 3Ti 4O 12Micro-nano level fiber is characterized in that: it comprises Elements C a, Cu, Ti and O, and they are 1:3:4:12 in molar ratio; , Fibre diameter is 200~300 nanometers.
2. a kind of CaCu as claimed in claim 1 3Ti 4O 12Micro-nano level fiber preparation method is characterized in that comprising the steps:
(1) under agitation condition, by weight, 100~200 parts of absolute ethyl alcohols, 1~5 part of calcium nitrate tetrahydrate and 2~10 part of one hydrated copper acetate are joined in the reaction vessel, isothermal reaction is 1~5 hour under 20~50 ℃ temperature condition, obtains solution A;
(2) under agitation condition; By weight; 5~30 parts of Vinylpyrrolidone polymers, 100~200 parts of absolute ethyl alcohols, 3~15 parts of spin finish aids and 3~15 parts of butyl(tetra)titanates are joined in the reaction vessel, and isothermal reaction is 1~3 hour under 20~50 ℃ temperature condition, obtains solution B;
(3) under agitation condition, solution B slowly is added drop-wise in the solution A, obtain electrostatic spinning solution;
(4) adopt electrostatic spinning process to obtain fiber;
(5) fiber that electrostatic spinning is obtained 50~70 ℃ dry 12~18 hours down, be heated to 900~1000 ℃ with 5~10 ℃/minute temperature rise rate again, and constant temperature 2~5 hours, obtain CaCu 3Ti 4O 12Micro-nano level fiber.
3. CaCu according to claim 2 3Ti 4O 12Micro-nano level fiber preparation method is characterized in that: described spin finish aid is acetate, TMAH, or a kind of in the Pottasium Hydroxide.
4. CaCu according to claim 2 3Ti 4O 12Micro-nano level fiber preparation method is characterized in that: electrostatic spinning process is 15~30 kilovolts of voltages, solidifies 5~15 centimetres of distances, and receiving trap is an aluminium foil.
CN 201110411790 2011-12-12 2011-12-12 A kind of CaCu3Ti4O12 micro-nano fiber and its preparation method Expired - Fee Related CN102515744B (en)

Priority Applications (1)

Application Number Priority Date Filing Date Title
CN 201110411790 CN102515744B (en) 2011-12-12 2011-12-12 A kind of CaCu3Ti4O12 micro-nano fiber and its preparation method

Applications Claiming Priority (1)

Application Number Priority Date Filing Date Title
CN 201110411790 CN102515744B (en) 2011-12-12 2011-12-12 A kind of CaCu3Ti4O12 micro-nano fiber and its preparation method

Publications (2)

Publication Number Publication Date
CN102515744A true CN102515744A (en) 2012-06-27
CN102515744B CN102515744B (en) 2013-07-24

Family

ID=46286888

Family Applications (1)

Application Number Title Priority Date Filing Date
CN 201110411790 Expired - Fee Related CN102515744B (en) 2011-12-12 2011-12-12 A kind of CaCu3Ti4O12 micro-nano fiber and its preparation method

Country Status (1)

Country Link
CN (1) CN102515744B (en)

Cited By (10)

* Cited by examiner, † Cited by third party
Publication number Priority date Publication date Assignee Title
CN103172363A (en) * 2012-09-10 2013-06-26 常州大学 Preparation method of a high dielectric constant perovskite-like CaCu3Ti4O12 (CCTO) pressure-sensitive material
CN103396548A (en) * 2013-08-14 2013-11-20 武汉一海数字工程有限公司 Preparation method of high-dielectric polyimide/calcium copper titanate nanowire composite material
CN104357955A (en) * 2014-10-28 2015-02-18 浙江大学 Preparation method of one-dimensional hollow porous structure calcium titanate nanofiber
CN105803579A (en) * 2016-04-06 2016-07-27 中国科学院深圳先进技术研究院 CaCu3Ti4O12 micro/nano-fibers and manufacturing method thereof
CN106111209A (en) * 2016-06-17 2016-11-16 扬州纳佰成纳米科技有限公司 The preparation method of tail gas denitration sub-micron fibers material
CN108017913A (en) * 2018-01-09 2018-05-11 哈尔滨理工大学 A kind of silicon rubber base direct current cables APPENDIX MATERIALSThe and preparation method thereof
CN108017861A (en) * 2017-10-09 2018-05-11 南通洪明电工科技有限公司 A kind of polymer-based dielectric composite material of coated with silica CaCu 3 Ti 4 O nanofiber and preparation method thereof
CN110475918A (en) * 2017-03-30 2019-11-19 捷恩智株式会社 The manufacturing method of metatitanic acid metal salt fiber
CN116516523A (en) * 2023-05-25 2023-08-01 常州工学院 A copper titanate calcium nickel composite fiber, its preparation method and its application in polyvinylidene fluoride based composite film
CN116892117A (en) * 2023-09-08 2023-10-17 江苏国望高科纤维有限公司 A kind of modified copper calcium titanate nanofiber and its preparation method and application

Citations (3)

* Cited by examiner, † Cited by third party
Publication number Priority date Publication date Assignee Title
CN101091111A (en) * 2005-12-23 2007-12-19 韩国科学技术研究院 Ultra-sensitive metal oxide gas sensor and fabrication method thereof
CN101698603A (en) * 2009-10-23 2010-04-28 西安交通大学 Method for preparing copper calcium titanate (CCTO) ceramic based on coprecipitation method
CN102191571A (en) * 2011-03-11 2011-09-21 长春理工大学 A preparation method of coaxial three-layer nano-cable NiO@SnO2@TiO2

Patent Citations (3)

* Cited by examiner, † Cited by third party
Publication number Priority date Publication date Assignee Title
CN101091111A (en) * 2005-12-23 2007-12-19 韩国科学技术研究院 Ultra-sensitive metal oxide gas sensor and fabrication method thereof
CN101698603A (en) * 2009-10-23 2010-04-28 西安交通大学 Method for preparing copper calcium titanate (CCTO) ceramic based on coprecipitation method
CN102191571A (en) * 2011-03-11 2011-09-21 长春理工大学 A preparation method of coaxial three-layer nano-cable NiO@SnO2@TiO2

Non-Patent Citations (4)

* Cited by examiner, † Cited by third party
Title
H.LORENZI ET AL: "Toxoplasma gondii ME49 hypothetical protein, mRNA", 《GENBANK:XM_002371928》 *
R.PARRA ET AL.: "Sol-gel synthesis of mesoporous CaCu3Ti4O12 thin films and their gas sensing respone", 《JOURNAL OF SOLID STATE CHEMISTRY》 *
付秀君等: ""真空吸附技术在风力发电玻璃钢件上的应用"", 《玻璃钢/复合材料》 *
崔广荣等: "微量元素及天然有机质对甜叶菊试管苗增殖和生长的影响", 《安徽科技学院学报》 *

Cited By (16)

* Cited by examiner, † Cited by third party
Publication number Priority date Publication date Assignee Title
CN103172363B (en) * 2012-09-10 2014-08-13 常州大学 Preparation method of a high dielectric constant perovskite-like CaCu3Ti4O12 (CCTO) pressure-sensitive material
CN103172363A (en) * 2012-09-10 2013-06-26 常州大学 Preparation method of a high dielectric constant perovskite-like CaCu3Ti4O12 (CCTO) pressure-sensitive material
CN103396548A (en) * 2013-08-14 2013-11-20 武汉一海数字工程有限公司 Preparation method of high-dielectric polyimide/calcium copper titanate nanowire composite material
CN103396548B (en) * 2013-08-14 2015-09-16 武汉一海数字工程有限公司 A kind of preparation method of high dielectric polyimide/CaCu 3 Ti 4 O nanowire composite
CN104357955A (en) * 2014-10-28 2015-02-18 浙江大学 Preparation method of one-dimensional hollow porous structure calcium titanate nanofiber
CN105803579A (en) * 2016-04-06 2016-07-27 中国科学院深圳先进技术研究院 CaCu3Ti4O12 micro/nano-fibers and manufacturing method thereof
CN106111209B (en) * 2016-06-17 2019-04-26 江苏纳佰成纳米科技有限公司 Preparation method of exhaust gas denitration submicron fiber material
CN106111209A (en) * 2016-06-17 2016-11-16 扬州纳佰成纳米科技有限公司 The preparation method of tail gas denitration sub-micron fibers material
CN110475918A (en) * 2017-03-30 2019-11-19 捷恩智株式会社 The manufacturing method of metatitanic acid metal salt fiber
CN108017861A (en) * 2017-10-09 2018-05-11 南通洪明电工科技有限公司 A kind of polymer-based dielectric composite material of coated with silica CaCu 3 Ti 4 O nanofiber and preparation method thereof
CN108017913A (en) * 2018-01-09 2018-05-11 哈尔滨理工大学 A kind of silicon rubber base direct current cables APPENDIX MATERIALSThe and preparation method thereof
CN108017913B (en) * 2018-01-09 2021-03-02 哈尔滨理工大学 A kind of silicone rubber-based DC cable accessory material and preparation method thereof
CN116516523A (en) * 2023-05-25 2023-08-01 常州工学院 A copper titanate calcium nickel composite fiber, its preparation method and its application in polyvinylidene fluoride based composite film
CN116516523B (en) * 2023-05-25 2025-02-07 常州工学院 A copper calcium nickel titanate composite fiber and its preparation method and application in polyvinylidene fluoride composite film
CN116892117A (en) * 2023-09-08 2023-10-17 江苏国望高科纤维有限公司 A kind of modified copper calcium titanate nanofiber and its preparation method and application
CN116892117B (en) * 2023-09-08 2024-01-02 江苏国望高科纤维有限公司 A kind of modified copper calcium titanate nanofiber and its preparation method and application

Also Published As

Publication number Publication date
CN102515744B (en) 2013-07-24

Similar Documents

Publication Publication Date Title
CN102515744B (en) A kind of CaCu3Ti4O12 micro-nano fiber and its preparation method
Julien et al. Fabrication of Li4Ti5O12 (LTO) as anode material for Li-Ion batteries
CN107151029B (en) A kind of sol-gel self-combustion synthesis preparation process of tetra phase barium titanate powder
CN102531580A (en) Nanometer barium-strontium titanate medium energy storage material coated by aluminum-silicon composite oxide and preparation method thereof
JP5521214B2 (en) Method for producing inorganic nanofiber
CN103214235B (en) A kind of preparation method of microwave dielectric ceramic materials
CN105295263A (en) Polymer matrix composite and preparation method thereof
CN101993086A (en) Preparation method of mono-disperse silicon dioxide micro-spheres
CN102041584B (en) Magnetic self-assembled mesoporous fiber and preparation method thereof
CN103145420A (en) Low-temperature sinterable vanadate microwave dielectric ceramic LiMVO4 and its preparation method
CN106012104A (en) A one-step method for the preparation of one-dimensional core-shell structure BaTiO3@Al2O3
CN103864420B (en) A kind of preparation method of microwave dielectric ceramic materials
KR20120083707A (en) Glass powder and method for preparing the same
CN109762278A (en) A kind of two-dimensional nano piece-polymer flexibility laminated film and preparation method thereof
CN115135606B (en) A method for preparing tetragonal barium titanate nanoparticles
CN109415265B (en) Dielectric ceramic material and preparation method thereof
CN103864425B (en) Preparation method of microwave dielectric ceramic material
CN102432283A (en) BaTiO of grain boundary layer type structure3Method for preparing composite membrane
CN107162055A (en) A kind of preparation method of vanadium niobates nano wire
CN103693957B (en) Method for preparing microwave dielectric ceramic material
CN105803579A (en) CaCu3Ti4O12 micro/nano-fibers and manufacturing method thereof
CN108774761A (en) A kind of the bismuth sodium titanate nanometer fiber and its synthetic method of electrostatic spinning technique synthesis
CN103342383B (en) A kind of preparation method of microwave dielectric ceramic materials
CN103342557B (en) Preparation method of microwave dielectric ceramic material
CN101788228B (en) Ceramic crucibles for calcining high-purity Nb2O5 and Ta2O5 powders

Legal Events

Date Code Title Description
C06 Publication
PB01 Publication
C10 Entry into substantive examination
SE01 Entry into force of request for substantive examination
C14 Grant of patent or utility model
GR01 Patent grant
C56 Change in the name or address of the patentee
CP02 Change in the address of a patent holder

Address after: Suzhou City, Jiangsu province 215137 Xiangcheng District Ji Road No. 8

Patentee after: Soochow University

Address before: 215123 Suzhou City, Suzhou Province Industrial Park, No. love road, No. 199

Patentee before: Soochow University

CF01 Termination of patent right due to non-payment of annual fee

Granted publication date: 20130724

Termination date: 20151212

EXPY Termination of patent right or utility model